Real world analysis on the efficacy and safety of anti-tumor necrosis factor therapy in patients with stricturing Crohn’s disease - Sudheer K. Vuyyuru; Bhaskar Kante; Peeyush Kumar; Pabitra Sahu; Saurabh Kedia; Mukesh Kumar Ranjan; Raju Sharma; Rajesh Panwar; Govind Makharia; Vineet Ahuja (Scientific Reports, 2021)
Abstract Crohn’s disease (CD) is often complicated by strictures and associated with increased risk for surgery. Inflammatory strictures respond to medical therapy, and anti-tumor necrosis factor (TNF) therapy is often used after the failure of steroids. However, data on efficacy of anti-TNF therapy in stricturing CD is limited. We retrospectively analysed the records of patients with stricturing CD who were treated with anti-TNF therapy and were prospectively followed from January 2005 to July 2020. Treatment success was defined as continuation of anti-TNF without the requirement for steroids or parenteral nutrition, switch to other anti-TNF, endoscopic dilation, surgery and severe adverse events leading to the withdrawal of anti-TNF. Fifty-nine patients were included [50-infliximab, 9-adalimumab; mean age-30.1 ± 15 years; males-69.5%; median disease duration-124 (range 30–396) months; median follow-up duration-42 (range 8–180) months]. Ileum was the most common site of stricture (69.5%), 20.3% of patients had colonic strictures, and 64.4% had multiple strictures. 55.9% of patients were steroid dependent and 37.3% were steroid refractory. The median duration of anti-TNF therapy was 14 (range 2–96) months, and 54.2% (n = 32) patients received concomitant immunomodulators. 88% improved with induction (11.8% primary non-response), secondary loss of response was seen in 52.2%, and the cumulative probability of treatment success at 1, 2 and 5 years was 69%, 51%, and 28% respectively. Anaemia at presentation predicted poor response. Only 30% of patients retained biologics on long-term (lack of response, cost, adverse events). 16.9% had adverse events, the commonest being reactivation of tuberculosis (5.1%). Anti-TNF therapy is associated with good short-term treatment success with modest long-term response in stricturing CD.